Participative management versus collective bargaining - Virmani, B. R. (New Delhi, India : Vision Books, 1988)
Indian context.
Spine title: Participative management vs. collective bargaining.
Includes index.
Bibliography: p. [146]-149.
Keywords: Industrial management -- Employee participation -- India -- Case studies; Collective bargaining -- India -- Case studies